ESTIMATION OF THE EFFICIENCY OF PREFERRED LENDING OF AGRICULTURAL PRODUCERS IN THE NORTH CAUCASUS FEDERAL DISTRICT - I. Rykova; A. Borisova; A. Yurieva (Вестник Северо-Кавказского федерального университета)
The article studied the effectiveness of preferential crediting of the agro-industrial complex of the North Caucasus Federal district, including the assessed impact of concessional lending designated banks, the main drawbacks of the current mechanism ofpreferential crediting, analyzed the indicators offinancial and economic activities of the recipients of the largest amounts of preferential loans. The relevance of this study is due to the need to improve the efficiency and optimization of federal budget expenditures aimed at implementing state policy in the field of suSort, development and increasing the competitiveness of the domestic agro-industrial complex. The scientiic and practical signiicance of the study lies in the development of new methodological aSroaches to assessing and demanding state suSort for agriculture through the implementation of a concessional lending mechanism, the results of which can be used in the course of optimizing, improving and increasing the efectiveness of measures of state suSort for the agro-industrial complex at the expense of the federal budget.